Optimal Scheduling Algorithm in Vehicular Real Time System - Sun, Yuan (Journal of networks, 2014)
In this paper, we mainly discuss the optimal scheduling algorithms in Low-end ECU and In-vehicle information system. For Low-end ECU, we propose an optimal scheduling algorithm. This algorithm can guarantee schedulability of mandatory parts in periodic tasks, guarantee aperiodic tasks and minimize the average scheduling error of optional parts in periodic tasks. In-vehicle information system is a multi-constraint real-time and non-real-time application coexisted application system. To meet the system scheduling requirements, a feedback algorithm based on the Constant Bandwidth Server is designed to control the fraction of CPU bandwidth allocation and a precise mathematical model is provided. Finally, the experimental results prove the effectiveness of our framework and algorithm. [PUBLICATION ABSTRACT]